The fitness factor : every woman's key to a lifetime of health and well-being - Callahan, Lisa. 4 0 16; 5 (Guilford, CT : Lyons Press, 2002)
Presents a guide to fitness for women, providing information on how exercise is the essential connection between fitness and lifelong health, including suggestions for increasing energy, controlling weight, preventing disease reducing stress, and more.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Health and hygiene. -- Exercise for women.;Physical fitness for women.;Women -- 20; 20; 2